Test the Activity of Vegetable Oils from Shorea Sumatrana SYM Against Bacteria Salmonella and Bacteria Eschericia Coli - Minarni - Minarni (Hasanuddin University, 2020)
Abstract. Tengkawang oil obtained from shorea sumatrana Sym fruit contains vegetable oil, extracts of tengkawang oil using n-hexane organic solvents. Tengkawang oil from shorea sumatrana fruit is a genus of dipterocarpacea family shorea which produces high value vegetable oil, is used for food preservatives, canker sores and diarrhea and as cosmetics. This study aims to determine the activity of salmonella bacteria, and escheria coli from tengkawang oil. Tengkawang oil was obtained by shocletation and bacterial testing by diffusion method with various oil concentrations (12.5,25,50 b/v) tengkawang oil mixed with bacterial supposition in NA medium and incubated at 37 0C for 18-34 hours to determine the level minimum inhibition (LMI) of culutation liquid results incubated on SDA (Sabourraud Dextrose Agar) media. The phytochemical screening test was carried out to determine the class of compounds contained in tengkawang oil from shorea Sumatrana. The results of the bacterial activity testing study showed that the LMI of concentrated salmonella bacteria was 12.5% b/v. MIC of 21, concentration of 25% b/v. LMI of 16 and concentration of 50% b/v. The LMI is 15, the test of tengkawang oil activity from shorea sumatrana fruit to Eschericia Coli is at a concentration of 12.5% b/v. LMI of 8, concentration of 25% b/v. LMI of 19 and concentration of 50% b/v. LMI is equal to 17. by using the control as a comparison if compared with the positive control of 10 and control negative equal to 7. The extracts of the pitochemical srening test showed that tengkawang oil from shorea sumatrana fruit contained penicillin, coumarin and flavonoids. The highest activity of tengkawang oil on salmonella bacteria was LMI at 12.5% b/v. The level of LMI was 21 activities using the larger Eschericia Coli LMI bacteria at a concentration of 25% b/v. LMI 19, from the activity test both bacteria were categorized as inhibiting the growth of Salmonella bacteria and Eschericia Coli bacteria.